FPGA-based cuckoo hashing for pattern matching in NIDS/NIPS - Tran, Thinh Ngoc; Kittitornkun, Surin (My University, 2007)
Pattern matching for network intrusion/prevention detection demands exceptionally high throughput with recent updates to support new attack patterns. This paper describes a novel FPGA-based pattern matching architecture using a recent hashing algorithm called Cuckoo Hashing. The proposed architecture features on-the-fly pattern updates without reconfiguration, more efficient hardware utilization, and higher throughput. Through various algorithmic changes of Cuckoo Hashing, we can implement parallel pattern matching on SRAM-based FPGA. Our system can accommodate the newest Snort rule-set, an open source Network Intrusion Detection/Prevention System, and achieve the highest utilization in terms of SRAM per character and Logic Cells per character at 15.63 bits/character and 0.033 Logic Cells/character, respectively on major Xilinx Virtex FPGA architectures. Compared to others, ours is more efficient than any other Xilinx FPGA architectures. © Springer-Verlag Berlin Heidelberg 2007.
Keywords: Cuckoo hashing; FPGA; NIDS; NIPS; Pattern matching